Understanding the influencing mechanism of users’ participation in live streaming shopping: A socio-technical perspective - Dong, Xueyan; Liu, Xu; Xiao, Xuan (Frontiers in Psychology, 2023)
Introduction In live streaming shopping, exploring the influencing mechanism of consumers’ participation is an important prerequi site for understanding consumer behavior in social commerce activities. The purpose of this study is to explore the relationship betw een technological and social factors (visibility, media richness, guidance shopping and real-time interactivity) in live streaming shop ping and consumers’ purchase intention. The mediating roles of attraction and cognitive assimilation were also examined. Methods This study collected 425 pieces of data through questionnaire survey. The structural equation model is established based on S-O-R frame. The hypothesis is tested by structural equation model. Results Our study found that that real-time interactive and media richness positively affect attraction; visibility, guidance shopping and media richness positive affect cognitive assimilation; cognitive assimilation and attraction positive affect consumers’ purchase intention; cognitive assimilation and attraction play a partial mediating role in the influence of technology and social factors on cons umers’ purchase intention of live streaming shopping. Discussion From the perspective of socio-technical, this study explores the influence mechanism of different influencing factors on consumers’ purchase intention in live streaming shopping. This study expands the application of IT affordance theory in the context of live streaming shopping, and reveals the mediating role of attraction and cognitive assimilation between social, technological factors and consumers’ purchase intention.